Furnace Control System Using the TCN4S Temperature Controller - Saputri Wahyuning Dewi; Gurum Ahmad Pauzi; Junaidi Junaidi; Sri Wahyu Suciyati (Journal of Energy, Material, and Instrumentation Technology, 2022)
In the academic world, especially in research activities at the University of Lampung, there are many things that the application of research requires an instrumentation system design to support these research activities. One example is used to melt metal or other materials. Therefore, this research aims to make a furnace using the Autonics TCN4S temperature controller. The basic configuration of a temperature regulation system consisting of temperature control is TCN4S, SSR (Solid State Relay), and Thermocouples. The results of this study indicate that the maximum temperature that can be achieved is 383°C within 710 seconds in an open space with an electric power of 1032.48 Watt and a strong current of 4.7 A so that the consumption of electricity consumption in the furnace is 0.2 KWh.